Multi-objective reactive power optimization based on chaos particle swarm optimization algorithm - He Xiao; Pang Xia; Zhu Da-rui; Liu Chong-xin (2013 2nd International Symposium on Instrumentation and Measurement, Sensor Network and Automation (IMSNA), 2013)
Reactive power optimization is closely related to voltage quality, network loss and it has great significance for the safety, reliability and economical operation of the power system. For shortage of traditional reactive power optimization, this paper establishes a multiple-objective reactive power optimization model which consists of minimum active power loss, minimum node voltage deviation, best static voltage stability and minimum reactive cost. To optimize four targets simultaneously, this paper has proposed a multi-objective reactive power optimization method which applies the chaotic particle swarm optimization algorithm based on Pareto solutions and finds the Pareto optimal solution sets of multi-objective optimization problems, then policy makers can make a scientific decision according to the actual situation. To prove the validity of the method proposed, this paper makes a multiple-objective reactive power optimization analysis for the IEEE30-bus system. The result shows that the method presented in this paper can achieve good results of reactive power optimization for decision makers to refer to.